IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIRQA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN TUMBUHAN - Beni Beni; Yakobus Bustami; Leliavia Leliavia (Program Studi Pendidikan Biologi, Fakultas Pendidikan Ilmu Eksakta dan Keolahragaan, IKIP Budi Utomo Malang, 2019)
The critical thinking skills of students in SMP Negeri 2 Sekadau Hilir were still low. This research aims to determine the effect of the jigsaw, reading, questioning, answering (JiRQA)type cooperative learning model on students critical thinking skills of SMP Negeri 2 Sekadau Hilir. The approach was quantitative in the form of quasi-experiment research. The instrument for measuring critical thinking skills using essay questions as many as 6 items. Data were analyzed using descriptive statistical analysis to determine mean and inferential analysis using the t-test. The results of the descriptive statistical analysis show that there was an increase in the mean value of pretest and post test critical thinking skills of the experimental class by 45.28% and the control class by 33.11%. The inferential statistical analysis results show that the probability value of students critical thinking skills of 0.00 is smaller than 0.05 so that it can be concluded that there was a significant effect of implementation JiRQA learning model on students' critical thinking skills.